2020
DOI: 10.3390/rs12152437
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sentinel-2 and Landsat 8 Images for Estimating Chlorophyll-a Concentrations in Lake Chad, Africa

Abstract: Much effort has been applied in estimating the concentrations of chlorophyll-a (Chl a) in lakes. The optical complexity and lack of in situ data complicate estimating Chl a in such water bodies. We compared four established satellite reflectance algorithms—the two-band and three-band algorithms (2BDA, 3BDA), fluorescence line height (FLH), and normalized difference chlorophyll index (NDCI)—to estimate Chl a concentration in Lake Chad. We evaluated the performance and applicability of Landsat-8 (L8) and Sentine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 64 publications
(56 reference statements)
4
40
0
4
Order By: Relevance
“…The spectral signature of Chl-a is characterized by strong absorption in the blue (443 nm) and red wavelengths (near 675 nm), and by high reflectance in the green (550-555 nm) and red-edge spectrum regions (685-710 nm) [42][43][44][45]. Existing studies have shown that the most suitable spectral range for monitoring suspended solids in water is 700-800nm [46].…”
Section: Spectral Analysismentioning
confidence: 99%
“…The spectral signature of Chl-a is characterized by strong absorption in the blue (443 nm) and red wavelengths (near 675 nm), and by high reflectance in the green (550-555 nm) and red-edge spectrum regions (685-710 nm) [42][43][44][45]. Existing studies have shown that the most suitable spectral range for monitoring suspended solids in water is 700-800nm [46].…”
Section: Spectral Analysismentioning
confidence: 99%
“…Sai số được tính toán dựa trên độ chênh lệch bình phương giữa giá trị thực tế (của các điểm đối chiếu) và 271 giá trị mô phỏng (trong mô hình hồi quy) theo công 272 thức (6). (7).…”
Section: U N C O R R E C T I O N P R O O Funclassified
“…nở hoa giữa ảnh radar và ảnh viễn thám vệ tinh5 ; nghiên cứu so sánh tính hiệu quả của các thuật toán của các ảnh vệ tinh WorldView, Sentinel 2, Landsat 8 và MERIS/OLCI6 hay nghiên cứu so sánh hiệu quả thuật toán 2BDA, 3BDA và NDCI giữa ảnh Landsat 8 và Sentinel 2…7 Các kết quả nghiên cứu chỉ ra rằng, Có hai mùa rõ rệt, mùa khô từ tháng12 đến hết tháng 04, mùa mưa từ tháng 05 đến hết tháng 11. Lượng mưa trung bình năm là 1.800-2.200 mm.…”
unclassified
“…The ESA's aim is that several Sentinel satellites [6] will act as Europe's eyes on Earth. At present, the following satellites are in orbit: Sentinel-1 (S1), which has a radar sensor installed, the Sentinel-2 (S2) satellite pair (Sentinel-2A and Sentinel-2B), which have optical sensors to study and monitor agriculture [7,8], and Sentinel-3, which has visual (VI) and near-infrared (NIR) sensors, for monitoring marine environments.…”
Section: Introductionmentioning
confidence: 99%